Thermal and kinetic analyses of Malaysian forest peat soil - Md Said, M. S.; Kannan, K.; Omar, R.; Mohd Tohir, M. Z.; Abdul Razak, M. (Springer Nature, 2024)
This study investigates thermal decomposition and kinetic parameters of Malaysian forest peat under oxidative and inert environments. Thermogravimetric analyses were conducted under non-isothermal conditions at different predetermined heating rates of 5, 10 and 20 °C/min. The pyrolysis curves demarcate peat decomposition by three main stages. First, evaporation of moisture and unstable organic compounds (29.94–176.11 °C). Second, organic matter pyrolysis (176.20–695.38 °C). Third, inorganic compound decomposition (695.46–998.38 °C). The activation energy obtained from the model-free methods for organic matter pyrolysis are 189 kJ/mol (Kissinger), 249 kJ/mol (Flynn–Wall–Ozawa), 251 kJ/mol (Kissinger–Akahira–Sunose) and 274 kJ/mol (Friedman). A scheme containing moisture evaporation and organic matter pyrolysis was proposed to simulate the pyrolysis process using DTG curve fitting method. In the combustion curves, the organic matter pyrolysis stage become two consecutive stages, i.e., the stage of organic matter decomposition (159.23–291.47 °C) and char oxidative combustion (291.49–513.97 °C). Moreover, the risk quantification was discussed based on the ignition temperature obtained from the TG and DTG profiles of peat samples. The results show that the ignition temperature increases with increasing heating rates and fires can be triggered by soaring soil temperatures.